Non-cystic fibrosis bronchiectasis in childhood: longitudinal growth and lung function. Issue 3 (3rd December 2008) - Bastardo, C M; Sonnappa, S; Stanojevic, S; Navarro, A; Lopez, P Mondejar; Jaffe, A; Bush, A
Abstract : Background: Non-cystic fibrosis (non-CF) bronchiectasis often starts in childhood with a significant impact on adult morbidity. Little is known about disease progression through childhood and the effect on growth and spirometry. This study reviews longitudinal lung function and growth in children with non-CF bronchiectasis. Methods: The case notes of patients with non-CF bronchiectasis were reviewed retrospectively. Patients were included if at least three calendar years of lung function data were available. Anthropometric measurements and annual spirometry were analysed over both two and four consecutive years. Changes over time were assessed using Generalised Estimating Equations. Results: Fifty-nine patients (31 boys) were identified. At baseline the median age was 8.2 years (range 4.8–15.8), the mean (SD) for height, weight and body mass index (BMI) for age z-scores were −0.68 (1.31), −0.19 (1.34) and 0.19 (1.38), respectively. At baseline, the mean (SD) z-score for forced expiratory volume in 1 s (FEV1 ) was −2.61 (1.82). Over 2 years (n = 59), mean FEV1 and forced vital capacity (FVC) improved by 0.17 (95% CI 0.01 to 0.34, p = 0.039) and 0.21 (95% CI 0.04 to 0.39, p = 0.016) z-scores per annum, respectively. Over 4 years there was improvement in height-for-age z-scores (slope 0.05, 95% CI 0.01 to 0.095, p = 0.01) but no improvement in other anthropometric variables. There was no change in spirometry (FEV1 slope 0.00, 95% CI −0.09 to 0.09, p = 0.999 and FVC slope 0.09, 95% CI −0.09 to 0.1, p = 0.859). Conclusions: Children with non-CF bronchiectasis show adequate growth over time. Lung function stabilises but does not normalise with treatment, underscoring the need for early detection and institution of appropriate therapy.